De la supervivencia al aprendizaje en combatientes (2013)
Login to the School of Nursing is an achievement, a desire for military combatants, many of them strive and strive to ensure that their commander's note and aspire to a quota for the Nursing Assistant course in Bogotá, leaving of the combat zone, close to his family, being in civilization for 18 months is a prize that has great value to develop in a multicultural environment. This person who is trained for survival, to fight must now be trained to save lives. In this context, the challenge presented to the Faculty of Nursing, creating the best Nursing Assistant to return to the combat zone and save the lives of his comrades.